Penerapan Digital Marketing Untuk Pengembangan UMKM di Desa Setro - Lutfy Richma Meylia; Kemal Maqda Faransyah; Ulfa Nurfia Nugrain; Ananda Trisnaning Widodo; Wahyu Wulan Sari; Nur Khayati; Devia Savitri; Eka Mey Pratiwi; Vega Famiartha Miarsyah Ali; Arif Mahya Fanny (Universitas PGRI Adi Buana Surabaya, 2022)
The Covid-19 pandemic has changed all forms of activities carried out by the community, the number of people who have experienced layoffs (PHK) has caused a lot of unemployment. There are many small traders who are generally food vendors who are sold at home. The number of MSMEs that have developed in this village are still implementing conventional sales, but the sales that have been carried out are also quite developed or those that have not yet developed. And the results of this activity are intended so that business owners are able to operate the application correctly so that people can benefit from the new things they get while increasing knowledge about digital marketing.